DEVELOPMENT AND VALIDATION OF A LEARNING STYLE SCALE FOR SECOND-YEAR MEDICAL STUDENTS AT CAN THO UNIVERSITY OF MEDICINE AND PHARMACY - Khanh Ly, Tong; Thanh Hong, Dang; Tran Quoc Loc, Truong; Hoang Ai Nhi, Nguyen; Vu Tien, Nguyen; Viet Hoang Huy, Phan (HNUE Journal of Science: Journal of Educational Science, 2026)
The study developed and validated an extended VARK scale of learning styles for second-year medical students at Can Tho University of Medicine and Pharmacy. A cross-sectional design was used with 300 students, including five factors: Visual, Aural, Read/Write, Kinesthetic, and Self-Assessment. Cronbach’s alpha was 0.917 (factors ranged from 0.839 to 0.875). EFA confirmed the structure (KMO = 0.909; p < 0.001), explaining 64.38% of variance. CFA supported the model (GFI = 0.938, CFI = 1.000, RMSEA = 0.000). Factor loadings (0.80–0.88) and low correlations confirmed convergent and discriminant validity. The addition of Self-Assessment improves multidimensionality and supports self-regulated learning.